Ideological Argumentation of the United States’Foreign Policy Identity - Liubov A. Fadeeva (RUDN Journal of Political Science)
Using the categorical apparatus created in Russian Political Science, the author describes the ideological argumentation of the US foreign policy identity. The works by American and Russian authors published in 2024 that examine concepts about the status, role, and place of the United States within the political debate on American identity provide the empirical data. The author claims that these publications offer analytical and factual support for the development of identity issues in the foreign policy context.